Pengaruh Cyberloafing terhadap Perilaku Kerja Inovatif Dimediasi oleh Komitmen Afektif - Agustina Paula Theresia Putri Lahallo; Wayan Gede Supartha (Institut Teknologi dan Sains Mandala, 2025)
The globalization of the workforce due to technological advancements creates challenges in attracting and retaining talented employees. Job demands trigger work actions; employees are required to perform work behaviors to meet standards. This research analyzes the influence of Cyberloafing on Innovative Work Behavior mediated by Affective Commitment. Based on the Theory of Planned Behavior. The quantitative associative study, conducted from December 2023 to January 2024, sampled 154 respondents from PT. Bank Pembangunan Daerah Bali. Data analysis was performed using SEM-PLS. Cyberloafing has no effect on Innovative Work Behavior, as employees use the internet without disrupting productivity or creativity. Affective Commitment positively influences Innovative Work Behavior, employees feel emotionally connected to the organization and support innovation. Cyberloafing negatively affects Affective Commitment. Cyberloafing negatively affects Innovative Work Behavior, fully mediated by affective commitment. Increasing Innovative Work Behavior through cross-divisional training, enhancing affective commitment with greater employee efforts, and regulating personal internet access reducing Cyberloafing.